Filling the constitutional lacunae concerning Islamic banking and finance litigations in Nigeria: Towards national harmony / Muhammad Bashir Alkali - Muhammad Bashir, Alkali (2016)
The objectives of this thesis are to fill the gaps in the Nigerian constitution 1999 relating to Islamic Banking and Finance (IBF) Litigations, using the system as an inter-faith bridge in pluralist Nigeria as well as using Alternative Dispute Resolution (ADR) to supplement the limited court system. The doctrinal methodology was the main method but some interviews were conducted to support it. This research found that the Constitution fell short of, among others, not providing original Jurisdiction to the Sharia Court of Appeal on matters of IBF; rather, it vested the same on the Federal High Court and appellate jurisdictions on the Federal Court of Appeal and the Supreme Court, whose constitutional requirements for the appointment of their Benchers do not include general knowledge of the Sharia. This work also found that amendments to the constitution, enactment of separate IBF Act, ADR, emulating Malaysia and the establishment of IBF Court or Tribunal will help in filling the lacunae in the Constitution. It was also found that having IBF is within constitutional right to worship and can be used as a bridge to unite Muslims and Christians in Nigeria. The study presented three contributions to legal research on IBF; Firstly, a microscopic view was made in the constitutional problems of incompetent Benchers in IBF litigations. Secondly, proposal was made for the use of ADR, special courts and laws to handle IBF matters. Thirdly, hypothesis was made to prove that IBF is the constitutional right of both Muslims and Christians. In conclusion, it is hoped that these findings and suggestions will be used by the government to legally enhance IBF operations in Nigeria for national harmony.